2018
DOI: 10.1021/acs.jpcb.7b10561
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Induced Thermal Equilibrium Intermediate and Counteracting Effect on Chemical Denaturation of Proteins

Abstract: When organisms are subjected to stress conditions, one of their adaptive responses is accumulation of small organic molecules called osmolytes. These osmolytes affect the structure and stability of the biological macromolecules including proteins. The present study examines the effect of a negatively charged amino acid osmolyte, glutamate (Glu), on two model proteins, ribonuclease A (RNase A) and α-lactalbumin (α-LA), which have positive and negative surface charges at pH 7, respectively. These proteins follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…The increase in temperature might weaken the intra‐chain interactions, thus the compressibility is reduced. Similar results are shown by both the proteins in the presence of stabilizing amino acid osmolytes as well . Hence, it is suggested that the thermal motions of surface‐exposed residues are constrained by the addition of osmolytes.…”
Section: Figuresupporting
confidence: 78%
See 1 more Smart Citation
“…The increase in temperature might weaken the intra‐chain interactions, thus the compressibility is reduced. Similar results are shown by both the proteins in the presence of stabilizing amino acid osmolytes as well . Hence, it is suggested that the thermal motions of surface‐exposed residues are constrained by the addition of osmolytes.…”
Section: Figuresupporting
confidence: 78%
“…Similar results are shown by both the proteins in the presence of stabilizing amino acid osmolytes as well. [20] Hence, it is suggested that the thermal motions of surface-exposed residues are constrained by the addition of osmolytes. Also, the increase in Arg concentration decreases the K s values consistently even in the presence of Gdm.…”
mentioning
confidence: 99%
“…Together, these data indicate that potassium glutamate (KGlu) is the primary cytoplasmic salt in E. coli . Furthermore, we learned that KGlu can stabilize soluble proteins, because Glu − interacts unfavorably with apolar side‐chains and amide groups . Given these facts, we examined the stability of SecA in KGlu solutions.…”
mentioning
confidence: 99%
“…Furthermore, we learned that KGlu can stabilize soluble proteins, because Glu − interacts unfavorably with apolar side-chains and amide groups. [19][20][21] Given these facts, we examined the stability of SecA in KGlu solutions. We report here that KGlu significantly stabilizes SecA, including its dimeric state, and increases its ATPase activity.…”
mentioning
confidence: 99%
“…The major advantage of using HHP over high temperature to study protein stability is the induction of less drastic structural changes ( Perrett and Zhou, 2002 ). As a chemical approach, the use of denaturing agents such as guanidine hydrochloride (GnHCl) is also relevant, since transitions between protein conformations and other parameters such as organization and aggregation can be addressed ( Syed et al., 2018 ; Anumalla and Prabhu, 2018 ; Niether et al., 2018 ; Bian and Ji, 2014 ). Therefore, the use of these structure-disrupting agents coupled with the possibility of monitoring the transition process between the native and unfolded states is useful to assess the difference in structural stability of apo and holo-bLf – i.e., the role of iron in the structure of this protein.…”
Section: Introductionmentioning
confidence: 99%